(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
When machining holes by burnishing, there is a direct relationship between the main parameter - the applied force and the geometric elements of the deforming rollers. This relationship can be determined by considering the force balance of the tool during operation. It is determined by the accuracy of the workpiece positioning and tool adjustment, and is expressed in the unevenness of the allowance, both in the transverse and in the proper section of the workpiece. The nature of the errors obtained and their magnitude depend, in addition to the accuracy of the relative position of the workpiece and the tool, on the scheme and operating mode. In order to simplify the analysis, it is necessary to neglect the friction forces during rolling and the magnitude of the elastic recovery of the material after burnishing. The tightness of the deforming elements is formed depending on the prescribed roughness of the surfaces, the type of material being processed and the type of tool. The rate of deformation of the machined holes is limited by the power of the machine and the design features of the deforming separator tool. This publication provides analytical dependencies for determining axial components of the deforming force using roller-ball separator tools for machining holes. Dependencies are derived for determining the optimal number of deforming elements ensuring a given accuracy of machined surfaces.The obtained analytical dependencies allow, under given production conditions, to ensure the necessary quality indicators of processing by changing the number of deforming elements and their radius in the tool design. From the condition for dynamic equilibrium of the support cone, the relationship between the cutting force and the deformation force can be revealed. This is a prerequisite for determining the transmission coefficients of the power chain for the two types of deforming elements - balls and rollers.